Coat Assembly Directs v-SNARE Concentration into Synthetic COPII Vesicles - Matsuoka, Ken; Morimitsu, Yasujiro; Uchida, Koji; Schekman, Randy (Molecular cell, 1998)
COPII proteins are required to create transport vesicles and to select cargo molecules for transit from the ER. A reconstituted liposome budding reaction was used to detect the capture and concentration of membrane-associated v-SNARE molecules into synthetic COPII vesicles. A novel glutathione-phosphatidylethanolamine conjugate (Glut-PE) was synthesized and incorporated into chemically defined liposomes to provide binding sites for GST hybrid proteins. Large liposomes containing bound cytoplasmic domains of the v-SNAREs, Sec22p or Bos1p, or of the ER resident proteins, Sec12p and Ufe1p, were exposed to COPII proteins and GMP-PNP. v-SNAREs but not resident proteins were concentrated in synthetic COPII vesicles generated from donor liposomes. We conclude that COPII proteins are necessary and sufficient for cargo selection and vesicle morphogenesis.